Comparing Student Learning From and Perceptions of Open and Commercial Textbook Excerpts: A Randomized Experiment - Clinton, Virginia; Legerski, Elizabeth; Rhodes, Bri (Frontiers in Education, 2019)
Open textbooks, which provide students with electronic access to texts without fees, have been developed as alternatives to commercial textbooks. Building on prior quasi-experiments, the purpose of this study is to experimentally compare an open and commercial textbook. College students (N = 144) were randomly assigned to read from an open or commercial textbook, answer questions about content, and indicate their perceptions of textbook quality. Learning was similar between textbook types. Perceptions differed in that the discussion of research findings was reported as higher quality in the open textbook while the visuals and writing were reported as higher quality in the commercial textbook. Neither perceptions of research findings nor visuals correlated with learning performance. However, perceptions of writing quality and everyday examples were correlated with learning performance. Findings may inform initiatives for open textbook adoption as well as textbook development.